Social and Cultural Barriers to Diabetes Prevention in Oklahoma American Indian Women - Christopher Taylor; Kathryn S. Keim; Alicia Sparrer; Jean Van Delinder; Stephany Parker (Centers for Disease Control and Prevention, 2004)
Introduction The prevalence of diabetes is disproportionately higher among minority populations, especially American Indians. Prevention or delay of diabetes in this population would improve quality of life and reduce health care costs. Identifying cultural definitions of health and diabetes is critically important to developing effective diabetes prevention programs. Methods In-home qualitative interviews were conducted with 79 American Indian women from 3 tribal clinics in northeast Oklahoma to identify a cultural definition of health and diabetes. Grounded theory was used to analyze verbatim transcripts. Results The women interviewed defined health in terms of physical functionality and absence of disease, with family members and friends serving as treatment promoters. Conversely, the women considered their overall health to be a personal issue addressed individually without burdening others. The women presented a fatalistic view of diabetes, regarding the disease as an inevitable event that destroys health and ultimately results in death. Conclusions Further understanding of the perceptions of health in at-risk populations will aid in developing diabetes prevention programs.